2021
DOI: 10.1177/02724316211058074
|View full text |Cite
|
Sign up to set email alerts
|

Be a Little Rude, but not too Much: Exploring Classroom Incivility and Social Network Position in Adolescents

Abstract: Classroom incivility is a critical concept relating to the academic and psychosocial well-being of children and youth. However, there has yet to be research investigating whether there are social benefits to this behavior in early adolescence. Therefore, the goal of this study was to explore the relationship between classroom incivility and measures of social network position, including incoming and mutual friendships, two forms of centrality, and social network prestige. We investigated network position of 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Such a finding is consistent with the hypothesis that bully perpetration reflects a social strategy, and that symptoms which reduce social approach behaviors (e.g., social anxiety) may reduce expected links between psychopathology (such as irritability) and perpetration (Thomas et al, 2018). Bully perpetration has been shown to confer certain types of social advantages, such as increased numbers of romantic partners (Provenzano et al, 2018;Volk et al, 2015), winning competitive endeavors (Dane et al, 2022), gaining social status (Spadafora et al, 2022), and deterring rivals (Cairns et al, 1988). While irritability is related to aggression writ large (Humphreys et al, 2019), bullying is unique in that it is targeted, goal-directed and inherently about social position (Volk et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Such a finding is consistent with the hypothesis that bully perpetration reflects a social strategy, and that symptoms which reduce social approach behaviors (e.g., social anxiety) may reduce expected links between psychopathology (such as irritability) and perpetration (Thomas et al, 2018). Bully perpetration has been shown to confer certain types of social advantages, such as increased numbers of romantic partners (Provenzano et al, 2018;Volk et al, 2015), winning competitive endeavors (Dane et al, 2022), gaining social status (Spadafora et al, 2022), and deterring rivals (Cairns et al, 1988). While irritability is related to aggression writ large (Humphreys et al, 2019), bullying is unique in that it is targeted, goal-directed and inherently about social position (Volk et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Classroom incivility refers to the range from unintentionally minor acts (e.g., packing up books before a lesson is over) to intentionally severe offenses (e.g., fighting with another student) (Spadafora & Volk, 2021). Adolescents establish higher social network positions by engaging in moderate levels of classroom incivility (Spadafora et al, 2021). However, some studies indicate that classroom incivility can lead to many negative consequences for adolescents, such as psychological distress, disengagement from lessons, dissatisfaction with institutions, performance decline, and serious antisocial behaviors (Caza & Cortina, 2007; Farrell et al, 2016; Hudgins et al, 2022; Spadafora et al, 2020, 2021; Turhan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents establish higher social network positions by engaging in moderate levels of classroom incivility (Spadafora et al, 2021). However, some studies indicate that classroom incivility can lead to many negative consequences for adolescents, such as psychological distress, disengagement from lessons, dissatisfaction with institutions, performance decline, and serious antisocial behaviors (Caza & Cortina, 2007; Farrell et al, 2016; Hudgins et al, 2022; Spadafora et al, 2020, 2021; Turhan et al, 2019). Most importantly, low‐intensity negative behaviors can be contagious (Foulk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent classroom incivility has begun to gain attention globally in recent research (Bіngӧl et al, 2018; Kinoshita & Sato, 2022; Nugroho et al, 2020; Spadafora et al, 2022; Susilawati, et al, 2020). Adolescent research has suggested that uncivil behavior in the classroom may not only disrupt classroom learning but may also have negative effects on the perpetrator.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent research has suggested that uncivil behavior in the classroom may not only disrupt classroom learning but may also have negative effects on the perpetrator. For example, previous research has demonstrated that engaging in higher levels of classroom incivility in adolescence is associated with lower levels of prosocial behavior and higher levels of emotional and conduct problems (Volk, 2016), fewer friendships (Spadafora et al, 2022), and antisocial traits (e.g., Honesty–humility: a willingness to exploit others) and behavior (e.g., aggression; Spadafora & Volk, 2021). Taken together, these findings highlight the importance of continuing to explore the potential implications of classroom incivility in adolescence.…”
Section: Introductionmentioning
confidence: 99%